Sex-specific outcomes with addition of defibrillation to resynchronisation therapy in patients with heart failure. Issue 10 (19th January 2017) - Barra, Sérgio; Providência, Rui; Duehmke, Rudolf; Boveda, Serge; Marijon, Eloi; Reitan, Christian; Borgquist, Rasmus; Klug, Didier; Defaye, Pascal; Sadoul, Nicolas; Deharo, Jean-Claude; Sadien, Iannish; et al.
Abstract : Objective: Among primary prevention patients with heart failure receiving cardiac resynchronisation therapy (CRT), the impact of additional implantable cardioverter defibrillator (ICD) treatment on outcomes and its interaction with sex remains uncertain. We aim to assess whether the addition of the ICD functionality to CRT devices offers a more pronounced survival benefit in men compared with women, as previous research has suggested. Methods: Observational multicentre cohort study of 5307 consecutive patients with ischaemic or non-ischaemic dilated cardiomyopathy and no history of sustained ventricular arrhythmias having CRT implantation with (cardiac resynchronisation therapy defibrillator (CRT-D), n=4037) or without (cardiac resynchronisation therapy pacemaker (CRT-P), n=1270) defibrillator functionality. Using propensity score (PS) matching and weighting and cause-of-death data, we assessed and compared the outcome of patients with CRT-D versus CRT-P. This analysis was stratified according to sex. Results: After a median follow-up of 34 months (interquartile range 22–60 months) no survival advantage, of CRT-D versus CRT-P was observed in both men and women after PS matching (HR=0.95, 95% CI 0.77 to 1.16, p=0.61, and HR=1.30, 95% CI 0.83 to 2.04, p=0.25, respectively). With inverse-probability weighting, a benefit of CRT-D was seen in male patients (HR 0.78, 95% CI 0.65 to 0.94, p=0.012) but not in women (HR 0.87, 95% CI 0.63 to 1.19, p=0.43). The excess unadjusted mortality of patients with CRT-P compared with CRT-D was related to sudden cardiac death in 7.4% of cases in men but only 2.2% in women. Conclusions: In primary prevention patients with CRT indication, the addition of a defibrillator might convey additional benefit only in well-selected male patients.